Locating Project Studios and Studio Projects. Issue 1 (2nd January 2016) - Slater, Mark
ABSTRACT: Via a longitudinal case study of a studio project (Middlewood Sessions, 2004–12), this research explores processes of music-making in the increasingly prevalent context of the project studio to give an insight into contemporary music-making practices. Predicated upon technologies of decreasing size but increasing processing power, project studios represent a diversification of musical creativity in terms of the persons and locations of music production. Increasingly mobile technologies lead to increasingly mobile practices of music production, which presents a challenge to the seemingly simple question: where is the project studio? In response, I propose an ontology of project-studio music-making that sets out what conditions have to be met for location, as an active proposition, to take place.